2018
DOI: 10.1097/01.ogx.0000547741.96802.c3
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use During the Perinatal Period in a State With Legalized Recreational and Medical Marijuana: The Association Between Maternal Characteristics, Breastfeeding Patterns, and Neonatal Outcomes

Abstract: (Abstracted from J Pediatr 2018;197:90–96) Cannabis is the most commonly used psychoactive substance in the United States, and recent estimates of the prevalence of cannabis use among pregnant women in the United States range between 3% and 16%. Population-based surveillance data from the National Survey on Drug Use and Health suggests that cannabis use among pregnant women in the United States has increased as much as 62% between 2002 and 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 0 publications
10
36
0
Order By: Relevance
“…Regarding substance abuse, our finding of nearly half of the adolescents reporting non-illicit substance abuse during pregnancy is in accordance with the literature [17,20]. The finding of a significant impact of substance abuse such as nicotine, cannabis and alcohol use [12][13][14] on birthweight is consistent with current findings in adult mothers. Substance abuse increases the risk of adverse events during pregnancy, and this risk could be a stronger target for preventive efforts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding substance abuse, our finding of nearly half of the adolescents reporting non-illicit substance abuse during pregnancy is in accordance with the literature [17,20]. The finding of a significant impact of substance abuse such as nicotine, cannabis and alcohol use [12][13][14] on birthweight is consistent with current findings in adult mothers. Substance abuse increases the risk of adverse events during pregnancy, and this risk could be a stronger target for preventive efforts.…”
Section: Discussionsupporting
confidence: 92%
“…Substance abuse during pregnancy is strongly associated with reduced birthweight: Maternal nicotine abuse during pregnancy leads to lower birthweightan average decrease of at least 200 g [12]. A significantly lower birthweight was also found to be related to the consumption of alcohol [13] and cannabinoids [14] during pregnancy. Substance abuse during pregnancy is more common in adolescent than in adult women [15].…”
Section: Introductionmentioning
confidence: 96%
“…Few studies have explored reasons for use during lactation, although some have noted that many people are likely to resume their prepregnancy use after giving birth. 53,54 Our findings provide empirical support for this observation, with many participants who used cannabis ceasing use during pregnancy and resuming in lactation. Another small group of participants chose to cease or forego lactation to resume cannabis use.…”
Section: Discussionsupporting
confidence: 66%
“…61 In a more recent study, prenatal cannabis use was associated with a 50% increased likelihood of low birth weight, independent of confounders, although no association was found for small for gestational age, preterm birth and neonatal intensive care unit admission. 62 Furthermore, another recent population-based retrospective cohort study that included 661 617 pregnancies reported that cannabis users (n = 9427) were twice as likely to have a preterm birth compared with non-users, after adjusting for confounding variables, including tobacco use. 63 Cannabis use can also affect breastfeeding as evidence suggests that THC and CBD can accumulate in breast milk.…”
Section: Impact Of Cannabis Use In Pregnancymentioning
confidence: 99%